Component restoring force identification for damage identification in vehicle suspension systems. (6th October 2008) - Haroon, Muhammad; Adams, Douglas E.
This paper presents a methodology for detecting and tracking the progress of mechanical damage in vehicle suspension system components. The area entrained by restoring force diagrams is proportional to the magnitude of internal forces acting between two points of a system, and the shape indicates the type of internal force. Mechanical damage causes a change in the internal force distributions of a system and, hence, the area and shape of the restoring forces. Operating acceleration response data are used to generate the restoring force curves. Individual damage mechanisms are identified by their particular effects on the internal loads.